2021
DOI: 10.1515/biol-2021-0118
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-overexpressing mesenchymal stem cells reciprocally regulate Th17/Treg cells by regulating the expression of IFN-γ

Abstract: Transforming growth factor (TGF)-β1 and mesenchymal stromal cells (MSCs) are two effective immunosuppressive agents for organ transplantation technology. This study aims to explore the molecular mechanism of TGF-β1-overexpressed MSCs on T cell immunosuppression. To achieve that, BM-MSCs were isolated from canine bone marrow, and their osteogenic differentiation and surface markers were detected. The TGF-β1 gene was transferred into lentivirus and modified MSCs (TGF-β1/MSCs) by lentivirus transfection. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It has been shown that TGF‐β1 secreted from mesenchymal stem cells functions in various aspects of the immune system. TGF‐β1 inhibits T cell, B cell, and NK cell function (Li et al., 2021; Niu et al., 2017). Hence, IWP‐2‐promoted TGF‐β1 mRNA expression in both normal and in vitro inflammation conditions could result in immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TGF‐β1 secreted from mesenchymal stem cells functions in various aspects of the immune system. TGF‐β1 inhibits T cell, B cell, and NK cell function (Li et al., 2021; Niu et al., 2017). Hence, IWP‐2‐promoted TGF‐β1 mRNA expression in both normal and in vitro inflammation conditions could result in immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the critical role of TGFβ in the modulation of the immunosuppressive ability of MSCs (27), there are conflicting arguments among researchers. Li et al demonstrated the immunosuppression potential of TGFβ1 overexpressed MSCs on co-cultured T lymphocytes (51). Conversely, Xu et al showed that TGFβ could decrease the immunosuppression capacity of MSCs (52).…”
Section: Discussionmentioning
confidence: 99%
“…Tregs are generated when antigens are presented by DCs to lymphocytes in the GALT during the eubiotic state ( Lathrop et al, 2011 ). Tregs produce anti-inflammatory cytokines, such as IL-10 and TGFβ, which are responsible for the inhibition of proinflammatory cytokine production, switching the immune response from Th1/Th17-dependent to Th2-dependent ( Li et al, 2021 ), and therefore quenching the immune reaction and promoting the repair process in the damaged tissue ( Mingomataj and Bakiri, 2016 ). Induced Tregs may also translocate into circulation and inhibit the inflammatory responses in the organism ( Weiner and Wu, 2011 ).…”
Section: Gut-brain Axis (Gba)mentioning
confidence: 99%